Meliore. Evolution of the Image of the Mother of God in Tuscany in the Second Half of the 13th Century on the Example of the Work of the Master - Pugacheva, Irina V. (Actual Problems of Theory and History of Art, 2019)
Meliore is a Florentine painter active in Tuscany in the second half of the 13th century. At different times about 10 works were attributed to his authorship, each of them containing the image of Our Lady. Nowadays the only confirmed artwork with his signature is a dossale with the Savior, the Virgin with the Child and three Apostles. Other works were attributed to Meliore by the art historians. These images represent a very remarkable group of monuments. His early works are quite simple, but in 20–30 years his style transformed approaching that of the early works of Duccio and Cimabue. The author suggests that the panel of Madonna with Child Enthroned from the Moscow Pushkin State Museum of Fine Arts (inv. 240) can be attributed to Meliore or to his milieu. Meliore’s artworks resemble the traditions of Pisa and Lucca (formed mainly under Byzantine influence), as well as that of Florence and Siena (the spirit of Coppo di Marcovaldo), especially in the later period. In the scholarly literature on the 13th century Italian painting the schools of Pisa, Florence or Siena are usually distinguished. Yet the group of images of Our Lady united under thename of Meliore, very different in their artistic qualities and emotional expression, allows us to think about these boundaries as conditional and to pose the question whether it is legitimate to talk about their separate formation in the second half of the 13th century.
Keywords: Meliore; Madonna and Child Enthroned; Italian painting in 13th century; Tuscany painting in 13th century; Madonna and Child Enthroned from the Pushkin Museum; Florentine painting in 13th century; Madonna and Child in Italian painting; Florentine painter in 13th century; Our Lady and Child Enthroned